PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. RIAU POS PEKANBARU - Fitria Winata; Jumiati Sasmita; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose is to know the effect of partial and simultaneous leadership, motivation, and work discipline on employee performance. This research was conducted at PT. Riau Pos Pekanbaru which is located at Jalan H. Soebrantas Km 10,5 Pekanbaru Kecamatan Tampan, Riau. The sample in this study amounted to 107 people by using random sampling method. In this study using quantitative descriptive with multiple linear regression analysis. Based on the results of research that has been implemented, leadership has an influence on employee performance with the tcount (5.488)> ttable (1.983) and the resulting significance value of 0.000. Motivation also has an effect on employee performance with the value of tcount (3.320)> ttable (1.983) and the resulting significance value of 0.00. And work discipline has an effect on employee performance with the value of tcount (4.105)> ttable (1.983) and the resulting significance value of 0.000. Thus known F count (76.706)> F table (2.69) with Sig. (0,000) <0.05. This means that simultaneously or simultaneously leadership, motivation and work discipline have an influence on employee performance at PT Riau Pos Pekanbaru. R value of 0.831 or 83.1% means there is a relationship between leadership, motivation and work discipline on employee performance at PT Riau Pos Pekanbaru. R Square value of 0.691 or 69.1% leadership, motivation and work discipline can affect employee performance at PT Pekanbaru Pekan Pekanbaru while the remaining 30.9% is influenced by other variables that are not used in this study. kkeywords : Leadership, Motivation,Work Discipline, Employee Performance.